2010
DOI: 10.2131/jts.35.571
|View full text |Cite
|
Sign up to set email alerts
|

5-Aminoimidazole-4-carboxamide-1-.BETA.-ribofuranoside (AICAR) prevents nuclear translocation of constitutive androstane receptor by AMP-activated protein kinase (AMPK) independent manner

Abstract: -The nuclear receptor superfamily consists of ligand-dependent transcription factors. Among them, constitutive androstane receptor (CAR) plays a key role in the detoxification of xenobiotics, inducing various drug-metabolizing enzymes including human CYP2B6 and its homologues of other species. AMP-activated protein kinase (AMPK) acts as an important energy sensor, being activated by an increased AMP/ATP ratio. CAR is activated by phenobarbital (PB) treatment. It has been recently reported that AMPK is involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…In a different study, Shindo et al (2007) demonstrated that metformin and AICAR induced CAR nuclear translocation but failed to induce hepatic CYP2B gene in mouse and rat livers. In contrast, another study revealed AICAR but not metformin prevented nuclear translocation of CAR and repressed PBinduced CYP2B expression in rat primary hepatocytes (Kanno et al, 2010).…”
Section: Discussionmentioning
confidence: 82%
“…In a different study, Shindo et al (2007) demonstrated that metformin and AICAR induced CAR nuclear translocation but failed to induce hepatic CYP2B gene in mouse and rat livers. In contrast, another study revealed AICAR but not metformin prevented nuclear translocation of CAR and repressed PBinduced CYP2B expression in rat primary hepatocytes (Kanno et al, 2010).…”
Section: Discussionmentioning
confidence: 82%
“…AMPK activation has previously been shown to promote phosphorylation and regulate the localization of constitutive androstane receptor (CAR) in cells293031. Therefore, we performed an in vitro kinase assay to determine if PXR was a direct target of AMPK.…”
Section: Resultsmentioning
confidence: 99%
“…The gluconeogenic transcription factor forkhead box transcription factor O1 (FoxO1) regulates the transactivation of both constitutive androstane receptor (CAR) and PXR target genes28. Also, AMPK regulates CAR, but the exact nature of this regulation remains unclear293031. To further delineate the crosstalk between the drug metabolism and energy metabolism pathways, we examined the glucose-dependent regulation of PXR in this study.…”
mentioning
confidence: 99%
“…A segment of the receptor interaction domain (RID) of steroid receptor coactivator 1 (SRC1) (Leo and Chen, 2000) (SRC1/RID, 569-781) was cloned into pcDNA5-GAL4/DBD. The expression plasmids for human CAR (hCAR)/LBD fused with GAL4/DBD were described previously (Kanno et al, 2010). The preparation of the XREM-driven luciferase reporter plasmid (XREM-luc) has been described elsewhere (Kanno et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…The expression plasmids for human CAR (hCAR)/LBD fused with GAL4/DBD were described previously (Kanno et al, 2010). The preparation of the XREM-driven luciferase reporter plasmid (XREM-luc) has been described elsewhere (Kanno et al, 2010).…”
Section: Methodsmentioning
confidence: 99%